An Assessement Extra-Curricular Activities and Primary School Pupils’ Academic Self-Efficacy in Gwale Local Government Area, Kano State of Nigeria - Mohammed, Auwalu Inusa; Dawaki, Muhammad Abdul; Idris, Maryam; Abdulhameed, Zikrullah; Bello, Hauwa; Abdullahi, Rabiu (NIU Journal of Humanities, 2017)
This paper attempted to look at the level of primary school pupils’ participation in extra-curricular activities; to find out the level of primary school pupils’ self-efficacy; and to assess the relationship between extra-curricular activities and primary school pupils’ self-efficacy in Gwale Local Government Area in the Kano State of Nigeria. It employed a cross sectional survey design, using quantitative approach. A sample of 400 pupils was taken from ten primary schools. To get the data, the researcher used self-administered questionnaire on extra-curricular activities and a standardized questionnaire of likert scale type, the Morgan-Jinks Students Efficacy Scale (MJSES).   The collected data were analyzed using the arithmetic mean and the Pearson’s Linear Correlation Coefficient. The findings were that the level of the pupils’ participation in extra-curricular activities was high, given the arithmetic mean of 2.8; pupils’ level of self-efficacy was high, given the grand arithmetic mean of 2.55. Based on these findings, the pupils’ participation in extra-curricular activities   was found to be high, there is need to make it higher due to the need of balancing studies with leisure, as well as the many advantages of extra-curricular activities. In doing this however, academics need not be compromised. Given the pupils’ high level of self-efficacy, there is need for them to be more confident and have very high self-efficacy because the more one feels the ability to do something, the more one is likely to do it; and given the finding that the pupils who highly participated in extra-curricular activities highly felt the confidence to perform well academically , and those who participated less in extra-curricular activities felt that they would not perform well academically, there is need for the two groups of pupils, the higher and lower participants in extra-curricular activities both to develop a feeling and confidence that they can perform very well academically, and hence work hard to achieve it. Keywords: Extracurricular activities, self-efficacy, primary education.